Cultural Value in The Ati Kebo Seunduhan Tradition Marriage of Demang Aryareja’s Development in Grantung Village, Purbalingga - S, Anissa Pristianingtyas; Birsyada, Muhammad Iqbal (IJTIMAIYA: Journal of Social Science and Teaching, 2022)
This study aims to determine: (1) The history of the tradition of Ati Kebo Seunduhan at the marriage of the descendants of Demang Aryareja in the village of Grantung, Purbalingga. (2) The process of implementing the tradition of AtiKebo Seunduhan at the marriage of the descendants of Demang Aryareja in the village of Grantung, Purbalingga. (3) Cultural value contained in the tradition Ati Kebo Seunduhan at the marriage of the descendants of Demang Aryareja in the village of Grantung, Purbalingga. The method used in this research is a qualitative research method with a descriptive approach. In this study, there are two types of data and data sources, namely primary data obtained through interviews and secondary data in the form of books, journals and theses. Data collection techniques used are observation, interviews and documentation. Data analysis techniques used are data collection, data reduction, data presentation, conclution and verification. The technique of checking the validity of the data used was source triangulation and theory triangulation. The result of this study indicate that: (1) The history of the tradition of AtiKeboSeunduhan on the marriage of the descendants of DemangAryareja has been carried out since the 19th century. (2) The process of implementing the Ati Kebo Seunduhan tradition begins with the purchase of buffalo hearts by men, the delivery of Ati Kebo Seunduhan to Demang Aryareja Cemetery and the distribution of Ati Kebo Seunduhan to relatives and neighbors. (3) The cultural values contained in the Ati Kebo Seunduhan tradition are the values of togetherness, kinship, and mutual cooperation.